Efeito dos óleos essenciais de thymus vulgaris e cinnamomun zeylanicum e seus componentes majoritários sobre o fungo fusarium oxysporum f.sp. lycopersici - Lima, Wilker Pinheiro (2018)
The tomato is the most consumed vegetable in the world, and its cultivation has a great economical and social importance. However, in its cultivation, the incidence of several diseases is favorable, among them the fusarium wilt, caused by Fusarium oxyspor